Action of the government of the DKI Jakarta province in the Jakarta flood control program claims by citizens (analysis of the decision of the PTUN number: 205/G/TF/2021/PTUN-JKT) - Yustiyah, Erma; Erliyana, Anna (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to analyze the judges' considerations in Decision No.205/G/TF/2021/PTUN-JKT related to the actions of the DKI Provincial Government Jakarta to implement the Jakarta Flood Control Program, which was sued by a citizen residing in South Jakarta. The Law on Government Administration provides an understanding of the actions of state officials or organizers to do and or not to take concrete actions in the context of administering the Government. In the Decision, the judge stated that there were no unlawful acts (PMH) by the authorities (onrechtmatige overheidsdaad). Still, in his judgment, the judge did not discuss the PMH argument by the rules (onrechtmatige overheidsdaad, which became petite.